Evaluation of toolbox safety training in construction: The impact of narratives - Eggerth, Donald E. (Am J Ind Med, 2018)
BACKGROUND: Construction is a dangerous industry with a large number of small businesses. Because they require minimal resources to deliver, toolbox talks may be an ideal training format for small construction contractors. METHODS: Eight toolbox talks were developed, each with two versions. One version of each toolbox talk was standard and one version included a narrative and discussion questions. Participants were randomly assigned to receive the standard or the narrative version. Pre- and post-intervention surveys measured demographics, workplace safety climate, and knowledge. The post-intervention survey also measured training impact. RESULTS: Including narratives with discussion questions significantly increased knowledge gain and led to increased training impact. Less experienced workers were more likely to gain knowledge and training impact compared to more experienced workers. There were no significant changes in workplace safety climate. CONCLUSIONS: The results suggest that including a narrative and discussion questions increases toolbox talk effectiveness.